Structural and Functional Asymmetry in Precentral and Postcentral Gyrus in Patients With Unilateral Chronic Shoulder Pain - Wei, Xiaoya; Shi, Guangxia; Tu, Jianfeng; Zhou, Hang; Duan, Yanshan; Lee, Chin Kai; Wang, Xu; Liu, Cunzhi (Frontiers in Neurology, 2022)
Objective: The purpose of this study was to explore the structural and functional asymmetry of precentral and postcentral gyrus in unilateral chronic shoulder pain (CSP) people utilizing magnetic resonance imaging (MRI). Patients and Methods: We collected structural and resting-state functional MRI data in 22 left-sided, 15 right-sided CSP patients, and 24 healthy controls. Here, we performed structural asymmetry and seed-based functional connectivity (FC) analyses. We extracted regional cortical thickness and surface area measurements from T1-weighted MRI images, using asymmetry indexes (AI) to assess asymmetries.We used DPABI for seed-based FC analysis, and selected unilateral-precentral and postcentral as the regions of interest. We also explored the relationships between altered brain asymmetry trends and clinical variables. Results: We found significant differences in surface area asymmetry of the precentral among three groups, the asymmetry indexes were negatively correlated with the visual analog scale score and positively correlated with Constant Murley scores (CMS) in the left-sided CSP group. Further, left postcentral showed increased FC with cingulate gyrus and left paracentral lobule, right postcentral showed increased FC with left caudate, left paracentral, and left postcentral. The right precentral showed increased FC with the cingulate gyrus, precuneus, and left paracentral. Besides, there was a positive correlation between right precentral-cingulate gyrus FC and CMS in the right-sided CSP group. Conclusion: Surface area and FC patterns asymmetry exist in precentral and postcentral gyrus in patients with unilateral CSP. Asymmetry trend is associated with pain severity and shoulder joint function impairment. Brain structural and functional asymmetry may be an important indicator for understanding the potential mechanism of chronic pain.